Penyuluhan kesehatan tentang kesadaran terhadap risiko tumor pada usia remaja - Kurniawaty, Nyiayu Fauziah; Maulani, Heni; Farida, Aida (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Any lump that is not normally there is called a tumor. Tumors are divided into two types, namely benign and malignant. Benign tumors generally do not cause death. Meanwhile, what is called a malignant tumor indicates a tumor that can invade the surrounding tissue, is able to move to other parts of the body and generally has a high mortality rate. In 2018 there were 18.1 million new cases with a death rate of 9.6 million deaths. 47 out of 100,000 teenagers have cancer. Cancer can be prevented by avoiding exposure to risk factors for malignancy such as radiation and chemicals. In addition, early detection plays an important role in reducing morbidity and mortality. There are still many cases that come to health workers at an advanced stage which have a worse prognosis when compared to diseases detected at an early stage. In this activity, we have explained several types of lumps that often affect teenagers and how to respond to them. The activity was coordinated by the staff of the Anatomic Pathology Section of the Faculty of Medicine, Sriwijaya University in collaboration with the Prabumulih City Government. At the end of the activity, the participants understood more about the importance of awareness of the risk of tumors in their teens.